2011
DOI: 10.1021/ic102472u
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Directing and Template Roles of Aromatic Molecules in the Self-Assembly Formation Process of 3D Holmium–Succinate MOFs

Abstract: Two new holmium-succinate frameworks have been synthesized by hydrolysis in situ of the succinylsalicylic acid under different hydrothermal conditions. Compound 1, [Ho(2)(C(4)H(4)O(4))(3)(H(2)O)(2)]·0.33(C(7)H(6)O(3)), P ̅i space group, has a novel structure composed by 1D-SBUs consisting of [HoO(9)] chains of polyhedra linked by the succinate ligands giving a 3D framework. Compound 2, [Ho(2)(C(4)H(4)O(4))(3)(H(2)O)(2)], also belonging to the P ̅i space group, has a denser structure. The role of the in-situ-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 59 publications
4
22
0
Order By: Relevance
“…The signals of as-prepared Tb-SA film agree with simulated XRD pattern of previously reported Holmium Succinate MOFs[42] and tin oxide (SnO 2 , JCPDS file No. 46-1088), the conductive coating component of FTO glass.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The signals of as-prepared Tb-SA film agree with simulated XRD pattern of previously reported Holmium Succinate MOFs[42] and tin oxide (SnO 2 , JCPDS file No. 46-1088), the conductive coating component of FTO glass.…”
supporting
confidence: 86%
“…Among them, the succinic acid (SA) presents interesting behaviors due to their conformational flexibility and coordination diversity [38], which is commonly used as the second ligands to fortify the MOF structure [39][40][41]. Previously reported Ln-succinate complexes indicated that succinic acid is an ideal ligand to forming flexible porous structure as well as being efficient energy donor [42,43], which is a promising ligand for luminescent sensing applications, but the luminescent sensing potential of Ln-succinate complex remains unexplored.…”
Section: Page 5 Of 33mentioning
confidence: 99%
“…According to the literature, the solvent could cause thermodynamic and kinetic effects in the formation of MOFs and could work as a ligand, reaction medium, both a ligand and reaction medium, or a structure‐directing agent (SDA). These effects could be changed by adding different aromatic compounds to the reacting mixtures . Park et al suggested that structure was formed not only by using a suitable linker, but also by the support of SDA as an amide‐like solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of employing succinic acid and salicylic acid as a mixed ligand system and Ho 3+ ion, 2D or 3D frameworks can be obtained depending on the synthesis conditions. For example, a 3D structure where the succinate ions play a structural role whereas a template one was determined for the salicylic acid, was firstly obtained by us .…”
Section: Structural and Topological Revisionmentioning
confidence: 99%
“…In the case of employing succinic acid and salicylic acid as a mixed ligand system and Ho 3+ ion, 2D or 3D frameworks can be obtained depending on the synthesis conditions. For example, a 3D structure where the succinate ions play a structural role whereas a template one was determined for the salicylic acid, was firstly obtained by us . This structure could be prepared either by in situ hydrolysis of succinylsalicylic acid or by adding succinic and salicylic acids in the reaction mixture; different times and temperatures of synthesis were rigorously probed to get the desired pure phase.…”
Section: Structural and Topological Revisionmentioning
confidence: 99%